2017
DOI: 10.1590/0004-282x20170122
|View full text |Cite
|
Sign up to set email alerts
|

Physicians are not well informed about the new guidelines for the treatment of acute stroke

Abstract: ARTICLE Physicians are not well informed about the new guidelines for the treatment of acute stroke ABSTRACTTreatment of cerebrovascular disease has advanced rapidly in the last two decades. Recent data has added challenges to the treatment of ischemic stroke in the acute phase. Objective: To evaluate the knowledge of physicians about the treatment of ischemic stroke in the acute phase. Methods: An online questionnaire was submitted to all physicians enrolled in the Regional Council of Medicine in Brazil. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 4 publications
0
0
1
2
Order By: Relevance
“…Thrombectomy can be performed after thrombolysis in eligible AIS patients who arrive within 4.5 h of stroke onset ( Academy of Medicine of Malaysia, 2021 ). Previously, it was reported that 86% of physicians were unaware of the possibility of thrombectomy with thrombolysis, which was higher compared to our study ( Gatto et al, 2017 ).…”
Section: Discussioncontrasting
confidence: 85%
“…Thrombectomy can be performed after thrombolysis in eligible AIS patients who arrive within 4.5 h of stroke onset ( Academy of Medicine of Malaysia, 2021 ). Previously, it was reported that 86% of physicians were unaware of the possibility of thrombectomy with thrombolysis, which was higher compared to our study ( Gatto et al, 2017 ).…”
Section: Discussioncontrasting
confidence: 85%
“…Los resultados mostraron que la mayoría de los entrevistados desconocían los tiempos de las ventanas terapéuticas para los tratamientos, y un 85 % afirmó que no realizaría la trombectomía asociada a la trombólisis. (35) En resumen, la investigación en trombólisis y trombectomía ha transformado el tratamiento del ACVi Agudo en las últimas décadas. Aunque los protocolos actuales son bastante uniformes en todo el mundo, es crucial que los médicos estén informados sobre estas prácticas para brindar la mejor atención posible a los pacientes.…”
Section: Ampliando Las Ventanas Terapéuticas Con Tecnología De Imágen...unclassified
“…Um estudo desenvolvido em um hospital público de Fortaleza, com a participação de 10 enfermeiros, vem em contraposição a este dado, visto que os participantes apresentaram conhecimento abrangente sobre tempo de início do tratamento, bem como os critérios de inclusão dos pacientes no uso de alteplase (Manivas, & Freitas, 2012). Concomitante a este dado, outro estudo realizado em Curitiba/PR, com 465 médicos participantes, evidenciou divergências entre os entrevistados sobre o tempo de atuação no evento isquêmico (Gatto, Koppe, Junior, & Zétola, 2017).…”
Section: [] Acredito Que Seria Muito Difícil De Realizar Devido a Resistência Da Equipe E Por Falta De Alguns Recursos Fundamentais (P8)unclassified